An observation tool for comprehensive pedagogy in content and language integrated learning (CLIL): examples from primary education - Wewer, Taina M (Colombian Applied Linguistics Journal, 2017)
This article on principles and practices in Content and Language Integrated Learning (CLIL) is also applicable for general foreign and second language instruction. Since there is no ‘one size fits all’ CLIL pedagogy, the origin of the article lies in the need of educators to obtain and exchange ideas of and tools for actual classroom practices (Pérez Cañado, 2017), and ensure that all key features of CLIL are present in instruction. Although there are a few handbooks available for launching CLIL and adopting CLIL pedagogy (e.g., Coyle, Hood, & Marsh, 2010; Mehisto, Marsh, & Frigols, 2008), these provide principles and general examples of content-based instruction at higher levels of education rather than more detailed advice on how to operate in the beginning phases with young language learners, hence the focus on primary education. The Observation Tool for Effective CLIL Teaching created by de Graaff, Koopman, Anikina, and Gerrit (2007) was chosen as the starting point and was complemented with three additional fields that were not markedly included in the original model: cultural aspects, affects, and assessment.